PERANCANGAN KATROL PADA CRANE PORTABLE KAPASITAS 300 KG GUNA ALAT BANTU DI BENGKEL PERALATAN AKADEMI MILITER - Juniarto Satryo; Sukahar; Suparyana (PPM Sdirjianbang Akademi Militer, 2022)
Military Academy equipment workshop one of the main tasks is to carry out the supply and maintenance of weapons, munitions and vehicle commodities to support the smooth running of education in the Military Academy environment. In the maintenance of vehicles often found a damaged vehicle engine so it needs to be repaired by lowering the vehicle engine. One of the tools needed is a crane. Crane is needed to move an item from one place to another. In the design of making this portable crane using steel rope type calculation according to United Rope Works Standard, Rotterdam Holland. Where the weight of the cargo lifted on this plan is 300 kg. Because the lifting is influenced by several factors, such as overload, dynamic conditions in operation and unexpected air changes, it is estimated that the additional load of 10% of the original load so that the weight of the cargo lifted to 330 kg. The maximum allowable stress value of steel rope is 362.946 kg, the permissible tensile stress is 59 kg/mm2, the cross-sectional area of steel rope is 0.088 cm2, the tensile stress that occurs on the rope is 41.24 kg / cm2. The calculation results are based on the selected type of steel rope according to United Rope Works Standard, Rotterdam Holland, which is 6 x 37 +1 fiber core. it is expected that planning steel rope is safe to use because the planned maximum tension (S) is smaller than the permit maximum tension ( S ) i.e. : 362.946 kg < 433.33 kg. And the planned tensile stress is smaller than the allowable tensile stress is : 41.24 kg/mm2< 59 kg/mm2.